Organogenesis in anise (Pimpinella anisum L.) - Khan Ullah Ishan, Rohit Saxena, Shailendra Nath Saxena (Journal of Spices and Aromatic Crops, 2012)
High frequency organogenesis was achieved in anise (Pimpinella anisum L.) using hypocotyl explants from in vitro germinated seedlings. Both cytokinins, benzylaminopurine and kinetin induced shoot regeneration but the effect of benzylaminopurine was more pronounced. High frequency shoot regeneration (45 shoots explant-1) was obtained on benzylaminopurine 1 mg l-1. Both cytokinins were also tested in combination with auxins (naphthaleneacetic acid/indoleacetic acid). Interaction of benzylaminopurine/kinetin with naphthaleneacetic acid/indoleacetic acid increased the length of regenerated shoots. Different kinds of callus morphology was observed but it had no relationship with regeneration potential. The regenerated plants were normal and healthy.